KEY ASPECTS IN THE IMPLEMENTATION OF GENDER-RESPONSIVE BUDGETING IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2026)
The article examines gender-responsive budgeting in Uzbekistan, its fiscal implications, and its role within public financial management. Using gender analysis and institutional assessment, the study highlights gender disparities, evaluates challenges in budget implementation, and draws on international experience to propose measures for integrating GRB into the national budget system.